Role of Udvartana, a diurnal Ayurveda practice in the prevention and management of diabetes mellitus (International Journal of Current Research in Physiology and Pharmacology, 2019)
Diabetes is among the most common lifestyle disorders of the modern era. The current approach towards its prevention and management is largely based on diet and lifestyle modifications. As increased body weight and serum lipids have been implicated in the risk factors of diabetes, measures to reduce them have a significant role to play. Udvartana described as a diurnal practice for health maintenance in Ayurveda plays an important role in the prevention and management of diabetes. Clinical studies have shown that Udvartana helps in reducing body weight as well as serum lipids. A review of the role of Udvartana in the prevention and management of diabetes is attempted here.Keywords: Diabetes; Udvartana; Body weight; Serum lipids.
Keywords: Diabetes; Udvartana; Body weight; Serum lipids.